2004
DOI: 10.4049/jimmunol.172.7.4308
|View full text |Cite
|
Sign up to set email alerts
|

Recombinogenic Phenotype of Human Activation-Induced Cytosine Deaminase

Abstract: Class switch recombination, gene conversion, and somatic hypermutation that diversify rearranged Ig genes to produce various classes of high affinity Abs are dependent on the enzyme activation-induced cytosine deaminase (AID). Evidence suggests that somatic hypermutation is due to error-prone DNA repair that is initiated by AID-mediated deamination of cytosine in DNA, whereas the mechanism by which AID controls recombination remains to be elucidated. In this study, using a yeast model system, we have observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
46
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(56 citation statements)
references
References 55 publications
10
46
0
Order By: Relevance
“…This is facilitated by its small size (24 kDa) and bona fide nucleocytoplasmic shuttling signals (52). These properties may also contribute to its ability to mutate the yeast CAN1 gene, as reported recently by Poltoratsky et al (53). In contrast, to accomplish retroelement restriction APOBEC3F and -G may never have to leave the cytoplasm, where they can access assembling retroelements (exogenous or endogenous).…”
Section: Discussionmentioning
confidence: 88%
“…This is facilitated by its small size (24 kDa) and bona fide nucleocytoplasmic shuttling signals (52). These properties may also contribute to its ability to mutate the yeast CAN1 gene, as reported recently by Poltoratsky et al (53). In contrast, to accomplish retroelement restriction APOBEC3F and -G may never have to leave the cytoplasm, where they can access assembling retroelements (exogenous or endogenous).…”
Section: Discussionmentioning
confidence: 88%
“…In vitro and in vivo experiments in E. coli have shown the transcription dependency of AID deamination and hypermutation, respectively (5)(6)(7)(8)12). A hyperrecombination and hypermutation effect of AID was also observed in yeast (28), but whether this was transcriptiondependent was not determined. In this work we show that hypermutation and hyperrecombination caused by AID in yeast are also transcription-dependent, confirming the hypothesis that the action of AID requires transcription of the target sequence (4,6,12).…”
Section: Discussionmentioning
confidence: 99%
“…To test this possibility, we confirmed that AID can induce hypermutation and hyperrecombination at low levels in yeast cells (28,29) and demonstrated additionally that this instability occurs in a transcription-dependent manner. Using yeast THO mutants as a way to generate suboptimal mRNP formation, we found that both hypermutation and hyperrecombination were strongly and synergistically increased in a transcription-dependent manner, with mutations primarily occurring in the NT strand.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…In contrast, copious genetic and biochemical evidence supports the DNA deamination theory that AID deaminates cytidine to uridine in DNA. Regarding genetics, overexpression of AID in Escherichia coli (4), yeast (5), cultured cell lines (6 -10), and mice (11) produced mostly C to T transitions in DNA, which likely resulted from a DNA polymerase replicating deoxyuridine (dU). Nonetheless, overexpression of APOBEC1 in E. coli also produced C to T transitions (12), suggesting that this assay is not specific for determining enzyme activity in mammalian cells.…”
mentioning
confidence: 99%